Drosophila immunity: a comparative analysis of the Rel proteins dorsal and Dif in the induction of the genes encoding diptericin and cecropin. - Gross, I.; Georgel, P.; Kappler, C.; Reichhart, J.M.; Hoffmann, J.A. (Nucleic Acids Research, 1996)
In Drosophila, bacterial challenge induces the rapid transcription of several genes encoding potent antibacterial peptides. The upstream sequences of the diptericin and cecropin Al genes, which have been investigated in detail, contain two, respectively one sequence element homologous to the binding site of the mammalian nuclear factor kappaB. These elements have been shown to be mandatory for immune-induced transcription of both genes. Functional studies have shown that these kappaB-related elements can be the target for the Drosophila Rel proteins dorsal and Dif. Here we present a comparative analysis of the transactivating capacities of these proteins on reporter genes fused to either the diptericin or the cecropin kappaB-related motifs. We conclude from our results: (i) the kappaB motifs of the diptericin and cecropin genes are not functionally equivalent; (ii) the dorsal and Dif proteins have distinct DNA-binding characteristics; (iii) dorsal and Dif can heterodimerize in vitro; (iv) mutants containing no copies of dorsal and a single copy of Dif retain their full capacity to express the diptericin and cecropin genes in response to challenge.